Reaching the global tuberculosis control targets in the Western Pacific Region - Pieter van Maaren; Bernard Tomas; Philippe Glaziou; Takeshi Kasai; Dongil Ahn
PROBLEM: In 1999, a tuberculosis (TB) crisis was declared in the Western Pacific Region. APPROACH: In response, WHO established the Stop TB Special Project, which sought to halve 2000 levels of TB prevalence and mortality by 2010 through first reaching the global 2005 TB targets. LOCAL SETTING: Particular issues in the region were low political commitment, inadequate numbers of staff (particularly of adequately trained staff) and a wide variation in TB burden between countries. RELEVANT CHANGES: WHO's leadership (especially the commitment of its Regional Director) and building of regional and national partnerships strengthened political and donor commitment. This accelerated the implementation of regional and national TB control plans, allowing the region to reach the 2005 targets for TB control. LESSONS LEARNED: The experience in the Western Pacific Region demonstrated that WHO's leadership was pivotal in generating the political commitment necessary to accelerate actions on the ground. The region's investment in building partnerships and a motivated workforce was an important contribution towards achieving the 2005 global TB targets.